AB0614 Prognostic Factors of Functional Outcome in Systemic Sclerosis-Associated Interstitial Lung Disease. (10th June 2014) - Le Gouellec, N.; Duhamel, A.; Faivre, J.-B.; Guillaume, L.; Sobanski, V.; Perez, T.; Hachulla, E.; Hatron, P.-Y.; Rémy-Jardin, M.; Launay, D.
Abstract : Background: Interstitial lung disease (ILD) is a frequent complication of systemic sclerosis (SSc) and is one of the first causes of mortality related to this disease. Screening sclerodermic patients for ILD at diagnosis and during the follow up is recommended. Its evolution is difficult to anticipate because predictive factors are not yet well established in SSc. Objectives: The aim of this study was to identify prognosis factors associated with the evolution of ILD-SSc. Methods: Clinical and biological data at the diagnosis of ILD, and serial pulmonary function tests (PFTs) were retrospectively collected in patients with ILD-SSc. We also analyzed the initial chest HRCT using the Wells score and the Goh staging system. The evolution of PFTs was modelled with linear mixed model with random coefficients. Results: Seventy-five patients (57 women; 23 diffuse scleroderma) with SSc complicated by ILD (18 extensive according to Goh) were included, with a mean follow up of 5 years and a median number of 5 PFTs. Mixed linear model showed that diffusing capacity of lung (DLCO) lowered significantly of 1, 45±0, 34%/year whereas forced vital capacity (FVC) remained stable. On bivariate analysis, patients with dyspnea class III or IV, baseline DLCO <80%, a greater extent of ILD and of reticular pattern had a lower FVC at baseline. The only parameter associated with a significant decline in FVC was a CRP above 10 mg/L. Patients with a lower baseline FVC and a greater extent of ILD and of reticular pattern had a lower DLCO at baseline. A past history of ulcers, a proportion of ground glass opacities above 70% and a baseline FVC >70% were associated with a decline of DLCO. Conclusions: Our study shows that modeling PFTs outcome in SSc-associated ILD is interesting to find prognostic factors. Initial CRP, reflecting IL-6 production, appears as an important prognostic factor for FVC evolution overtime. Conversely, SSc and autoantibodies subtypes were not prognostic factors for PFTs evolution in our study. ILD extension is associated with worse PFTs at baseline but is not associated with DLCO of FVC decline. References: Ohtsuka, J Dermatol 2010; 37(9): 801–6 Liu, Arthritis Care & Res 2013; 65(8):1375-80 Muangchan, Arthritis Care & Res 2012; 64(9): 1405–14 De Lauretis, J Rheumatol 2013;40(4):435-46 Goh, Am J Respir Care Med 2008; 177(11): 1248-54 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3866